2023
DOI: 10.3389/fpubh.2023.1088728
|View full text |Cite
|
Sign up to set email alerts
|

How to not revert to type: Complexity-informed learnings from the pandemic response for health system reform and universal access to integrated care

Abstract: This article is part of the Research Topic ‘Health Systems Recovery in the Context of COVID-19 and Protracted Conflict’.BackgroundCOVID-19 has highlighted existing health inequalities and health system deficiencies both in Ireland and internationally; however, understanding of the critical opportunities for health system change that have arisen during the pandemic is still emerging and largely descriptive. This research is situated in the Irish health reform context of Sláintecare, the reform programme which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Conversely, while the COVID-19 pandemic has placed major pressure on the health and social care systems in all countries, the pandemic was not considered as a catalyst for enduring novel ways of working. We found that the pandemic highlighted and exacerbated existing weaknesses within and across the health and social care systems in all three countries, confirming observations reported elsewhere [24]. Perhaps surprisingly, given that we sampled three countries with different approaches to driving integration, we did not identify particular integrated system governance models that showed themselves to be more (or less) resilient to recovering from the pandemic.…”
Section: Discussionsupporting
confidence: 87%
“…Conversely, while the COVID-19 pandemic has placed major pressure on the health and social care systems in all countries, the pandemic was not considered as a catalyst for enduring novel ways of working. We found that the pandemic highlighted and exacerbated existing weaknesses within and across the health and social care systems in all three countries, confirming observations reported elsewhere [24]. Perhaps surprisingly, given that we sampled three countries with different approaches to driving integration, we did not identify particular integrated system governance models that showed themselves to be more (or less) resilient to recovering from the pandemic.…”
Section: Discussionsupporting
confidence: 87%
“…While the 2017 ‘Sláintecare’ health policy outlined a 10‐year structural health service reform plan for Ireland, towards universal healthcare 19 and had cross‐party political support, the commitment to full and timely implementation is still unclear. Parker et al 20 highlight how the COVID‐19 pandemic led to system‐wide, rapid pivots in care organisation and provision, and that we should use the key learnings from this to inform the shift towards universal healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…This study forms one of the workstreams within the Health Research Board (HRB)-funded Foundations' research project that aims to harness key learnings from Ireland's health system response to COVID-19 with a view to informing the implementation of Ireland's ten-year health reform plan, Sláintecare 17,29,38,[64][65][66] .…”
Section: Methodsmentioning
confidence: 99%
“…This intersection gains heightened relevance within the Irish context, where the interplay between universalist COVID-19 policies and a substantial private sector holds particular significance. The emergence of UHC principles played a central role in responding to the COVID-19 crisis 17,18,28,29 . Although additional capacity from the private sector was deemed necessary, the primary emphasis remained on upholding an equitable public sector-driven pandemic response 30 .…”
Section: Introductionmentioning
confidence: 99%